2019
DOI: 10.1155/2019/3140183
|View full text |Cite
|
Sign up to set email alerts
|

ILC2s Induce Adaptive Th2-Type Immunity in Acute Exacerbation of Chronic Obstructive Pulmonary Disease

Abstract: To investigate the effect of ILC2s on Th2-type adaptive immunity during the acute exacerbation of chronic obstructive pulmonary disease (AECOPD), the study enrolled healthy people, stable COPD patients, and AECOPD patients. Flow cytometry was used to detect Th1, Th2, and ILC2 in the peripheral blood and CD80 and MHC II levels on ILC2. The mRNA levels of GATA3, RORα, and CRTH2 of ILC2s were detected by RT-PCR. In addition, ILC2s from the peripheral blood of AECOPD patients were cocultured with CD4+ T cells from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 50 publications
2
43
0
Order By: Relevance
“…There were higher levels of IL-4, IL-6, and IL-8 in serum or sputum from AECOPD than those from the control subjects. 25 However, IL-4 and IL-8 cannot judge the different type of AECOPD as biomarkers. Higher levels of sputum and serum IL-6 were observed in eosinophilic AECOPD than those in neutrophilic AECOPD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There were higher levels of IL-4, IL-6, and IL-8 in serum or sputum from AECOPD than those from the control subjects. 25 However, IL-4 and IL-8 cannot judge the different type of AECOPD as biomarkers. Higher levels of sputum and serum IL-6 were observed in eosinophilic AECOPD than those in neutrophilic AECOPD.…”
Section: Discussionmentioning
confidence: 99%
“…Th2 cells and ILC2 cells then produce IL-5 and IL-13. 25,27 IL-5 plays a central role in stimulating the growth, differentiation, and maturation of eosinophils in the bone marrow and also is implicated in the function and survival of eosinophils. 28 Clinical trials have shown that mepolizumab, which is a monoclonal antibody against IL-5, can reduce the exacerbation rate of COPD by inhibiting blood eosinophilia.…”
Section: Discussionmentioning
confidence: 99%
“…It is involved in regulation of inflammatory and immune responses as well as mucous hypersecretion [ 125 , 126 ]. Eosinophils have shown secretion of IL-13 under GM-CSF and/or IL-5 stimulation [ 127 ] and ILC2 cells are also able to secrete IL-5 and IL-13 under stimulation of IL-33 and IL-25 [ 128 ]. ILC2s have been found increased in patients with stable COPD or during acute exacerbation [ 46 ].…”
Section: Pathophysiology and Molecular Mechanismsmentioning
confidence: 99%
“…However, only ILC2s in humans express PD‐1 but not ILC1s and ILC3s 252 . The lungs of acute exacerbation of chronic obstructive pulmonary disease (AECOPD) patients also show the ILC2‐mediated Th2 immune response induction 253 . These patients also show the increase in systemic IL‐4 levels and the number of ILC2s in peripheral blood.…”
Section: Ilc and T Cell Cross‐talk During Allergic Asthma And Other Cmentioning
confidence: 99%
“…These patients also show the increase in systemic IL‐4 levels and the number of ILC2s in peripheral blood. These ILC2s also overexpress MHC‐II and CD80 as compared to the control group, and serve as APCs to stimulate CD4 + T cell immune response in AECOPD 253 …”
Section: Ilc and T Cell Cross‐talk During Allergic Asthma And Other Cmentioning
confidence: 99%